Pengaruh Work Life Balance Terhadap Organizational Citizenship Behavior Melalui Psychological Empowerment Sebagai Variabel Intervening Pada Karyawan di PT Aura BIna Sejahtera - Kusuma Ambarsari, Linda; Rozaq, Khoirur (Universitas Negeri Surabaya, 2025)
This study aims to determine and analyze the effect of work-life balance on Organizational Citizenship Behavior through psychological empowerment as an intervening variable. This study is a causal study using a quantitative approach, with a population of 53 employees. The sampling technique used is a non-probability sampling technique, namely the saturated sample technique. The statistical analysis method in this study is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) supported by SmartPLS 4.1 computer software. The results of this study indicate that there is a positive and significant influence of work-life balance on Organizational Citizenship Behavior, a positive and significant influence of work-life balance on psychological empowerment, a positive and significant influence of psychological empowerment on Organizational Citizenship Behavior, and psychological empowerment can mediate work-life balance on Organizational Citizenship Behavior. Companies that want to improve Organizational Citizenship Behavior need to pay more attention to work-life balance through psychological empowerment.